THE VALIDITY OF GOLD INSTALLMENT CONTRACTS IN ISLAMIC BANKS: : An Analysis of KHES and DSN-MUI Fatwas - Hamdanil; Alwadipa, Bagus Pria (Institut Agama Islam Negeri Metro, 2025)
This study examines the dynamics of gold installment plans at Islamic banks with reference to the DSN-MUI fatwa as a legal basis, because this scheme attracts public interest as an alternative to sharia investment but still often causes uncertainty in the contract. The research method used is normative law of a qualitative nature and literature review, utilizing DSN-MUI Fatwa No. 77/DSN-MUI/VI/2010, contemporary fiqh literature, journal articles, and Islamic bank documents, which were analyzed using content analysis. The study revealed that the fatwa guarantees physical ownership of gold and the establishment of a fixed margin, but in practice, certificates are often issued without physical gold, margins are rarely explained transparently, and post-contract price fluctuations are not optimally accommodated. A comparison with contemporary fiqh scholars shows similarities in the principles of haqiqi, takhsis, and the prohibition of riba ‘uyuniyah, but the fatwa is less flexible regarding extreme price adjustments. An ideal operational model requires a gradual delivery mechanism, cost transparency, and customer protection in accordance with the maqashid syariah. Although the fatwa is consistent with Sharia principles, there is a gap between theory and practice that could potentially harm customers. Recommendations include the implementation of gradual physical delivery, transparent pricing, revision of fatwas related to market price references, and the development of bank SOPs to ensure Sharia compliance and asset protection.